Sensorineural hearing loss and risk of stroke: a systematic review and meta-analysis - Masoud Khosravipour (Nature Portfolio, 2021)
Abstract The aim of this systematic review and meta-analysis study was to clarify the effects of sensorineural hearing loss (SNHL) on the incidence of stroke. In line with this, PubMed, Scopus, Web of Science, and ScienceDirect databases were searched using related keywords and MeSH terms from inception to March 1, 2020. Out of the 1961 initial records, eight cohort studies comprising 4,564,202 participants were included, and their qualities were assessed using the Newcastle-Ottawa Scale (NOS). Then, the random-effects model was used to pool HR (95% CI) for risk of stroke; and heterogeneity was presented with I2 index. Subgroup analysis and publication bias tests were performed, and the pooled HR (95% CI) of stroke in SNHL was estimated as 1.31 (1.08, 1.53) for the unadjusted model and 1.33 (1.18, 1.49) for the adjusted model. Subgroup analysis indicates a significantly higher risk of stroke in patients with sudden SNHL (SSNHL) in comparison to age-related HL (ARHL) both in the unadjusted model, [HR = 1.46; 95% CI (1.08, 1.63)] versus [HR = 1.14; 95% CI (0.64, 1.65)], and in the adjusted model, [HR = 1.44; 95% CI (1.15, 1.74)] versus [HR = 1.29; 95% CI (1.24, 1.34)]. Our study showed that patients with SNHL face a higher risk of stroke than those without SNHL. It is necessary to perform hematologic and neurological examinations to help clinicians detect patients who are potentially at risk for stroke.